2017
DOI: 10.1007/s10571-017-0567-0
|View full text |Cite
|
Sign up to set email alerts
|

The PGC-1α Activator ZLN005 Ameliorates Ischemia-Induced Neuronal Injury In Vitro and In Vivo

Abstract: Oxidative stress is a great challenge to neurons following cerebral ischemia. PGC-1α has been shown to act as a potent modulator of oxidative metabolism. In this study, the effects of ZLN005, a small molecule that activate PGC-1α, against oxygen-glucose deprivation (OGD)- or ischemia-induced neuronal injury in vitro and in vivo were investigated. Transient middle cerebral artery occlusion (tMCAO) was performed in rats and ZLN005 was administered intravenously at 2 h, 4 h, or 6 h after ischemia onset. Infarct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…It was determined that the pretreatment time of ATEO for cytoprotection was 48 h (Supplementary Figure 2). Similar results were observed in pretreatment of ZLN005 (2 μM), a PGC-1α activator with known antioxidant capability [26]. Additionally, ATEOtreated cultures did not show abnormal nuclear morphology in PC12 cells (Figure 2(c)), which was consistent with the finding in safe concentration range.…”
Section: Ateo Protected Pc12 Cells From H 2 O 2 -Mediated Injurysupporting
confidence: 87%
See 1 more Smart Citation
“…It was determined that the pretreatment time of ATEO for cytoprotection was 48 h (Supplementary Figure 2). Similar results were observed in pretreatment of ZLN005 (2 μM), a PGC-1α activator with known antioxidant capability [26]. Additionally, ATEOtreated cultures did not show abnormal nuclear morphology in PC12 cells (Figure 2(c)), which was consistent with the finding in safe concentration range.…”
Section: Ateo Protected Pc12 Cells From H 2 O 2 -Mediated Injurysupporting
confidence: 87%
“…In this study, the cellular mechanism of ATEO against oxidative stress was investigated. PC12 cells were selected as the cell model due to their phenotypic characteristics of sympathetic neurons [25,26]. We evaluated whether ATEO had a beneficial effect on H 2 O 2 -stressed PC12 cells, including a PGC-1α-mediated increase of cell viability, decrease of ROS level, and upregulation of antioxidant protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Multiple studies have shown that OGD-induced neuronal oxidative damage can be significantly attenuated by activating the Nrf2/HO-1 pathway. [27][28][29] AMPK regulates cellular energy metabolism, and its activation helps bring metabolic processes into balance. AMPK activates the Nrf2/ HO-1 signaling axis, suggesting tight cooperation between signaling pathways controlling cellular redox and energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…ZLN005 regulates PGC‐1α transcription through muscle cell‐specific transcription factors such as MEF2 and improves insulin resistance and dyslipidemia in db/db diabetic mice (Zhang, Shao, et al, ; Zhang, Zhou, et al, ). Additionally, ZLN005 exhibits neuroprotective and retinoprotective effects in mice (Satish, Philipose, Rosales, & Saint‐Geniez, ; Xu et al, ). However, the cardioprotective effect of ZLN005 is dependent on SIRT1 but not PGC‐1α activation (Li et al, ).…”
Section: Effect Of Antiaging Drugs On Pgc‐1α Activationmentioning
confidence: 99%